Timothy (Phleum pratense L.) as a ley grass in northern Finland - Nissinen, Oiva (AK, 1998)
Timothy (Phleum pratense L.) is the most widely cultivated ley crop in northern Finland. For this reason, most of the research work on leys carried out at the Agricultural Research Centre of Finland's Lapland Research Station (66o 35' N) has been centred on the development of its management practices. Although timothy is relatively resistant to frost, water-logging and ice scorch, in northern Finland, in many years winter damage to stands caused by snow moulds, Sclerotinia borealis and Typhula spp. result in great economic losses. The new varieties, Iki and Tuukka originating from snowy regions are more resistant to low-temperature fungi than those of southern origin. It is not possible to fully utilize the most rapid growth phase of timothy in spring summer for silage due to rapid changes in chemical composition. The increase in dry matter yield has been fastest, 230 kg/ha/day, and dry matter yield has increased from 3000 kg to 5300 kg/ha during the period of about 10 days from first visible heads until full heading. Simultaneously the crude protein content has decreased from 17.3 to 11.8 % and the organic matter digestibility has decreased from 74 to 66 % on an average. The winterhardiness and productivity of timothy are best maintained if the first cut is not carried out until the full head stage has been reached. Production of timothy swards is also significantly reduced by taking four cuts instead of one or two cuts. Dry matter yields of pasture swards have been 4250 kg/ha, which is only 67 % of the yields from hay swards, 6340 kg/ha.
Keywords: Ka; timotei; nurmet; timothy; Phleum pratense L.; varieties; winter damage; snow moulds; dry matter yield; crude protein content; organic matter digestibility